DFT study on reaction mechanism of di-tert-butylphenol to di-tert-butylhydroxybenzoic acid - Jin, Neng-Zhi; Zhang, Qi-Bin; Liu, Rong; Zhou, Pan-Pan (Structural chemistry, 2022)
Experimental studies on the Kolbe–Schmitt reaction and its side reactions have made great progresses; however, the relative theoretical studies fall behind. In order to study the mechanism of the Kolbe–Schmitt reaction with 2,6-di-tert-butylphenol and 2,4-di-tert-butylphenol as reactants, we carried out theoretical calculation studies at the M06-2X/Def2-SVP/SMD level of theory using the Gaussian 09 D.01 software package. For the reactant 2,6-di-tert-butylphenol, there is a dynamic equilibrium between the main product and side product, which can rapidly transform into each other at 160 °C by crossing the Gibbs free energy barrier of 14.1 kcal/mol. Moreover, the relative Gibbs free energy of the main product and side product is close; both of them may be observed in the experimental system. However, for 2,4-di-tert-butylphenol, the main product is thermodynamically favorable due to its lower Gibbs free energy, while the side product is kinetically favorable due to the lower activation energy barrier; the main product and the side product compete with each other. We hope the study can shed light on the Kolbe–Schmitt reaction.